Decreasing the indications for radical nephrectomy: a study of multifocal renal cell carcinoma - Sorbellini, Maximiliano; Bratslavsky, Gennady (Frontiers in Oncology, 2012)
Abstract: Multifocal Renal Cell Carcinoma (RCC) has been reported in 5-25% of cases worldwide. Although management of patients with multifocal RCC has not been clearly defined, presence of multifocal renal masses has often been considered a reason for performing radical nephrectomy. This study reviews the world literature to provide an accurate estimate of the prevalence of multifocal RCC and evaluate the existing data on treatment outcomes of multifocal RCC with nephron-sparing techniques. A Pubmed search of the literature was performed for articles in the English language using the following terms for the query: “multifocal RCC”, “multifocality and RCC”, “multicentric RCC”, or “bilateral RCC”. The references of the published articles were also reviewed for additional publications. Articles that did not specify exclusion of patients with familial RCC or known hereditary RCC syndromes were excluded to allow for accurate estimation of multifocality prevalence. In total, nine articles were selected to be included in our study and form the basis of the current analysis. Weighted averages were used to calculate the prevalence of multifocality. Finally, we have reviewed the literature on oncologic outcomes of patients with recurrent multifocal RCC treated with nephron sparing surgeries (without exclusion of hereditary patient population). Multifocal RCC was found in 6.8% of cases of renal cell carcinoma (373 of 5433 patients). Bilaterality in the setting of multifocality was reported in 11.7% of cases. Of all cases reported in the study cohort, only 10% (37 out of 373 patients) were treated by partial nephrectomy. The remainder of the cohort underwent radical nephrectomy. The review of the literature showed that the use of nephron-sparing techniques in patients with recurrent multifocal disease did not compromise oncologic outcomes, despite the need for reoperation in certain cases. In conclusion, multifocal RCC remains a prevalent entity. While many clinicians still o